New exponential stability criterion for switched linear systems with average dwell time. (September 2019) - Gao, Yi; Wen, Jiwei; Peng, Li
In this article, the partition of state space is investigated based on the average dwell time theory, and a novel switching condition is proposed. Under the switching condition and strategy, a switched system where all subsystems are unstable is globally exponentially stabilized. Compared with the existing literature, the conclusion is less conservative and more general. Consequently, the conditions appropriate for this exponential stability issue are derived and a computational procedure to solve the bilinear matrix inequality problems and admissible average dwell time is provided. Finally, two numerical examples are used to show the validity and effectiveness of the proposed methods.